Tasawuf Dalam Pandangan Orientalis: Antara Objektivitas Akademik Dan Bias Peradaban - Mausulul Arham; Ibnu Dwi Cahyo; Jemmy Harto; Achmad Maftuh Sujanan; Erdi Rujikartawi (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2026)
This research discusses the orientalist view of Sufism and the objectivity of the study of orientalism in understanding Islamic spirituality. Sufism is one of the important dimensions of Islamic teachings that emphasizes the purification of the soul, the formation of morals, and the approach of oneself to Allah. In its development, Sufism became the object of attention of Western orientalists who sought to study the history, teachings, and figures of Sufi through various academic approaches. The study of orientalism made a major contribution to the development of Islamic studies, especially through the translation of classical manuscripts, scientific research, and the introduction of Sufism to the Western world. However, the study also raises various debates because some orientalists are considered to have a civilizational bias in understanding Sufism. Some orientalists view Sufism as the result of the influence of traditions outside of Islam such as Neo-Platonism, Christianity, Hinduism, and Persia, while Muslim scholars assert that Sufism has a strong foundation in the Qur'an and Hadith. Data were obtained from books, journals, scientific articles, and works by Muslim orientalists and scholars related to the research theme. The analysis technique used is descriptive-critical analysis to understand the contribution as well as criticize the objectivity of the study of orientalism on Sufism. The results of the study show that orientalism has two different sides, namely making a great academic contribution to the study of Sufism while giving birth to interpretations that are sometimes influenced by Western perspectives and interests. Therefore, the study of orientalism on Sufism needs to be understood critically and proportionately so that Sufism is still understood as an integral part of Islamic teachings and is inseparable from its spiritual, theological, and moral dimensions.